The vocational training and the christian vocation of service of teachers of religious education of the diocesan office of catholic education of Huánuco - Blas C., Crispín (2013)
The precedent of the study the ecclesiastic document Gravissimum Education is on the Christian education of the Council Vatican the II, it expresses the right of every person to an integral education, this is, physical, moral, intellectual, sexual, social and religious. There are repeated the purposes and the characteristics of the education it christens: the human complete formation and the progress in the life of the new man in Christ. There are exposed the rights and duties of the parents and the importance of the family in the education, as well as those of the civil society and the Church. The principal aim of the present study was to determine the level of influence of the Christian vocational training in the development of the vocation of service of the teachers of religious education of the Diocesan Office of Huánuco Catholic Education. Applying a survey to anexample of 62 teachers manand women who were working to level of the coordination of the Diocesan Office Of Catholic Education of Llata district, Huamalíesprovince, region Huánuco, managed to establish the following conclusion that yes exists a direct and significant influence between the vocational training and the vocation of the service of the teachers of religious education of the diocesan office of Huánuco catholic education.